Mass spectrometry protein tests: ready for prime time (or not). (2nd January 2017) - Nedelkov, Dobrin
ABSTRACT: Introduction : Mass spectrometry has played an important role in protein biomarker discovery. Yet, very few of the candidate biomarkers have been validated, and mass spectrometry-based protein tests have not made a significant inroad into clinical laboratories. Areas covered : Offered here is a unique perspective on the future of mass spectrometry protein tests, in view of the following determinants: the true demand for such clinical tests, end-users requirements, platforms and systems design, sample preparation bottlenecks, analytical and clinical validation, and regulatory approval. Expert commentary : Fresh thoughts and attitudes toward MS protein tests are required in order to move them toward clinical utilization and diagnostic use en masse, with critical emphasis on content, simplicity and cost. In its current format and state of the art, they are simply not ready for prime time.